2019
DOI: 10.1021/acs.jpcc.9b07907
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Alkanes in Zeolites LTA and FAU: Quasi-Equilibrated Thermodesorption Supported by Molecular Simulations

Abstract: Adsorption of n-alkanes from pentane to decane (C5−C10) in zeolites LTA (ITQ-29 and 5A) and faujasite (FAU, dealuminated high-silica Na-FAU, NaY, and NaX) as well as branched hexane isomers in FAU was investigated by means of experimental quasi-equilibrated temperature-programmed desorption and adsorption (QE-TPDA) and theoretical Monte Carlo molecular simulations. A novel QE-TPDA method of studying porosity provided highquality desorption−adsorption profiles and adsorption isobars of hydrocarbons. A unique tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…HS-FAU is Na + exchanged dealuminated high-silica faujasite with Si/Al > 100, NaY is Na + exchanged faujasite with Si/Al ≈ 2.61, while NaX is Na + exchanged faujasite with Si/Al ≈ 1.06. The characteristics of these materials, i.e., low-temperature nitrogen adsorption and powder X-ray diffraction, were reported in our previous works. , …”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…HS-FAU is Na + exchanged dealuminated high-silica faujasite with Si/Al > 100, NaY is Na + exchanged faujasite with Si/Al ≈ 2.61, while NaX is Na + exchanged faujasite with Si/Al ≈ 1.06. The characteristics of these materials, i.e., low-temperature nitrogen adsorption and powder X-ray diffraction, were reported in our previous works. , …”
Section: Methodsmentioning
confidence: 87%
“…For methanol, we used a 4 °C min –1 ramp for all materials, while for water, 2 °C min –1 for NaY and NaX and 1 °C min –1 for HS-FAU were used. It is worth mentioning that adsorption measurements of water in NaX and HS-FAU were reported in our previous work. , Between each cycle, they were kept at RT for 2 h. More details on data reduction and methodology are available in the literature …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the molecules of n-alkanes are located only in ZIF-8 cages, similarly to LTA zeolites. 43 The QE-TPDA experimental technique was also used to study surface-related adsorption on the ZIF-8. Nanocrystalline ZIF-8 desorbs signicant amounts of pre-adsorbed n-nonane at relatively low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of n-alkanes in ZIF-8 takes place in the cavities of this material, in a very similar way that we found for LTA-type zeolites. 43 The molecules prefer to locate close to the framework atoms, so the centres of cages are less occupied. Either way, no specic sites for adsorption of C5C9 n-alkanes can be found in the structures of ZIF-8 (Figure S10S14), which was conrmed by the analysis of radial distribution functions (Figure S17).…”
Section: Adsorptionmentioning
confidence: 99%